1971
DOI: 10.1039/j39710002347
|View full text |Cite
|
Sign up to set email alerts
|

The photosensitised oxidation of amines. Part II. The use of dyes as photosensitisers: evidence that singlet oxygen is not involved

Abstract: The products from the dye-photosensitised oxidation of a number of aliphatic amines are reported. Tertiary amines reacted efficiently to give carbonyl compounds and imines. Secondary and primary amines are relatively unreactive. Only those amines were reactive which were capable of photobleaching the dye in the absence of oxygen.N-Alkylanilines were found to be unreactive. The oxidations sensitised by Rose Bengal were found to increase in efficiency as the concentration of oxygen in the reaction mixture was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…Another possible explanation of the decreased oxygen inhibition in Nsubstituted amide/acrylate formulations is an oxygen consumption process similar to that described for amines (4,(11)(12)(13)(14)(15)(16)(17). For NVP or NVCL, hydrogen atom abstraction would likely occur on the ring carbon alpha to the nitrogen, followed by consumption of dissolved oxygen through coupling of the pyrrolidonyl radical with an oxygen molecule.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another possible explanation of the decreased oxygen inhibition in Nsubstituted amide/acrylate formulations is an oxygen consumption process similar to that described for amines (4,(11)(12)(13)(14)(15)(16)(17). For NVP or NVCL, hydrogen atom abstraction would likely occur on the ring carbon alpha to the nitrogen, followed by consumption of dissolved oxygen through coupling of the pyrrolidonyl radical with an oxygen molecule.…”
Section: Discussionmentioning
confidence: 96%
“…A discussion of the kinetics of free-radical polymerization and competing reactions in the context of oxygen inhibition was given in a previous report (3). A number of techniques have been utilized to combat oxygen inhibition, including use of high intensity lamps/high cure dosages (4)(5)(6)(7)(8), inert atmospheres/sandwiching materials (9,10% and additives such as amines, which have been shown to consume oxygen by a photo-oxidation process (4,(11)(12)(13)(14)(15)(16)(17). In our initial studies (3,18) we confirmed earlier reports (19,20) that NVP dramatically increases the relative rates of acrylate polymerization in air at low light intensities and that a reversible complexation occurs between oxygen and NVP as observed in the UV absorption spectrum (21).…”
Section: Introductionmentioning
confidence: 99%
“…O2· can also arise via a sensitizer radical anion formed by one‐electron oxidation. The generation of O2· that is in equilibrium with HO2·, as a side product of type I photosensitization, is a more prevalent process . Reactions of O2· can occur with highly oxidizing radicals (addition, reduction) or when there is not an appropriate substrate for its conversion into H 2 O 2 by dismutation (spontaneous or mediated by superoxide dismutase in cells), the precursor of highly reactive ·OH.…”
Section: Type I and Type Ii Photosensitized Oxidation Reactionsmentioning
confidence: 99%
“…ZnO or Fe/ZnO nanoparticles can recruit O 2 in the initiation mechanism to prevent inhibition of the initiating radicals [24]. Additives such as amines and silanes that consume dissolved O 2 in the system are the most common ways of preventing oxygen inhibition [25,26]. In addition, weak mechanical properties and deprived accuracy of stereolithography resin (SLR) are widespread problems for most desktop-level SLA techniques, restricting their utilization as functional materials [27].…”
Section: Introductionmentioning
confidence: 99%